Small Explosions: Bold and Combustible New Monologues for All Ages and Genders - Szymkowicz, Adam (Rowman & Littlefield Publishers, 2023)
One minute: that’s all the time an actor needs to make a scorching impression—to pull in an audience, make them care, laugh, cry, remind them that life is worth living, or help them forget that life is hard. Small Explosions collects more than ninety entirely new monologues from acclaimed playwright Adam Szymkowicz (Hearts Like Fists, Clown Bar, Pretty Theft). Short, punchy, and thoroughly memorable, they traverse the extremes of heartbreak and joy, epiphany, and bewilderment, across a range of moods and voices. Perfect as audition pieces or training exercises, they hit hard, make their mark, and just as quickly get out of the way, leaving an indelible impression.